HLA tissue status in patients with gluten sensitive enteropathy - Ahmet TEZEL; Aysel ÜLKER; Arzu ENSARİ; Çağlar BAYSAL; Klara DALVA; Ülkü DAĞLI; Azmi SERİN; Hülya ÖVER; Canan ALKIM (Turkish Journal of Gastroenterology, 2019)
-